Estimation of annual spatial variations in forest production and crop yields at landscape scale in temperate climate regions. Issue 2 (9th November 2014) - Ruidisch, M.; Nguyen, T. T.; Li, Y. L.; Geyer, R.; Tenhunen, J.
Abstract: Simulating regional variations in gross primary production (GPP) and yields of major land cover types is complex due to differences in plant physiological properties, landscape topography, and climate gradients. In our study, we analyzed the inter‐annual and inter‐regional variation, as well as the effect of summer drought, on gross primary production and crop yields of 9 major land uses within the state‐funded Bioenergy Region Bayreuth in Germany. We developed a simulation framework using a process based model which accounts for variations in both CO2 gas exchange, and in the case of crops, growth processes. The results indicated a severe impact of summer drought on GPP, particularly of forests and grasslands. Yields of winter crops, early planted summer grain crops as well as the perennial 2nd generation biofuel crop Silphium perfoliatum, on the other hand, were buffered despite drought by comparatively mild winter and spring temperatures. We estimated regional yield increases from SW to NE, suggesting a comparative advantage for these crops in the cooler and upland part of the region. In contrast, grasslands and annual summer crops such as maize and potato did not exhibit any apparent regional pattern in the simulations. The 2nd generation bioenergy crop exhibited significantly higher GPP and yields compared to the conventional bioenergy crop maize, suggesting that cultivation of S. perfoliatum should be increased for economic and environmental reasons, but additional study of the growth of S. perfoliatum is still required.